Oxidative dual C–H thiolation of imidazopyridines with ethers or alkanes using elemental sulphur. Issue 55 (26th June 2017) - Zhang, Jun-Rong; Liao, Yan-Yan; Deng, Jian-Chao; Feng, Kai-Ying; Zhang, Min; Ning, Yun-Yun; Lin, Zi-Wei; Tang, Ri-Yuan
Abstract : Dual C–H thiolation reactions using elemental sulphur remain a challenge. Abstract : Dual C–H thiolation reactions using elemental sulphur remain a challenge. This communication discloses an oxidative radical dual sp 2 /sp 3 C–H thiolation strategy for the coupling of imidazopyridines with ethers or alkanes using elemental sulphur.